2018
DOI: 10.1007/s10151-018-1814-1
|View full text |Cite|
|
Sign up to set email alerts
|

Topical antimicrobial prophylaxis in colorectal surgery for the prevention of surgical wound infection: a systematic review and meta-analysis

Abstract: Each of these interventions appears to be effective in decreasing SSI, but the number of studies for each is small and the quality of evidence is very low to moderate. Within the various outcomes of GRADE assessment, even a moderate classification suggests that further studies may well have very different results.. No randomized trials exist of combinations of two or more of the above interventions to see if there is a combined effect. Future studies should make sure that the antibiotic used preoperatively is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Similarly, an RCT [ 18 ] that included 291 patients who underwent laparoscopic colorectal surgery at a single center also failed to prove the efficacy of the gentamicin-collagen sponge. However, in a recent meta-analysis [ 5 ], a sensitivity analysis of abdominal wounds revealed that a gentamicin-collagen sponge could reduce SSI in colorectal surgery (RR, 0.38; 95% CI, 0.20–0.72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an RCT [ 18 ] that included 291 patients who underwent laparoscopic colorectal surgery at a single center also failed to prove the efficacy of the gentamicin-collagen sponge. However, in a recent meta-analysis [ 5 ], a sensitivity analysis of abdominal wounds revealed that a gentamicin-collagen sponge could reduce SSI in colorectal surgery (RR, 0.38; 95% CI, 0.20–0.72).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the colorectal surgery field, a large-scale randomized control study [ 4 ] of gentamicin-containing sponges failed to prove their effectiveness. Nevertheless, a recent meta-analysis that excluded this study due to high risk of bias reported that, based on sensitivity analyses of abdominal wounds, gentamicin-collagen sponges could reduce the risk of SSI (relative risk [RR], 0.38; 95% CI, 0.20–0.72) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the current WHO SSI prevention guidelines and subsequently updated meta-analyses could not resolve methodological and generalisability issues of the underlying trials. 23 The included trials were mostly at high risk of bias, contained narrow groups of patients, and did not include any patients undergoing contaminated surgery. 9 FALCON addresses these issues, by being at low risk of bias, being larger than all the combined randomised trial data for clean-contaminated and contaminated or dirty surgery to date, and being the only multicountry randomised trial done exclusively in LMICs, where the burden of SSI is highest.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for prophylactic application of local antibiotics to wounds (of any kind) in other surgical specialties is conflicting, with variability in their efficacy between specialties and procedure types. 43,44 Currently, their routine use in vascular groin wounds cannot be recommended.…”
Section: Discussionmentioning
confidence: 99%